Discussion on health promotion behavior of patients with long COVID based on COM-B model and qualitative research on influencing factors (基于COM-B模型探讨新型冠状病毒感染长期症状患者健康促进行为及影响因素的质性研究) - WU Meng (吴蒙); DING Yao (丁瑶); XUE Hui (薛辉); MU Yanli (牟艳丽); CHEN Lijin (陈丽金); LIU Ying (刘莹); LUO Li (罗丽) (中西医结合护理)
Objective To explore the health promotion behavior and its influencing factors of patients with long COVID, and to provide reference for the construction of intervention programs. Methods Totally 15 patients with long COVID were interviewed by semi-structured sampling method, and the interview data were analyzed according to Colaizzi seven-step analysis method to extract the theme. Results A total of three topics were obtained: healthy behavior ability (including limited cognition, low self-control, physical ability and health literacy), healthy behavior motivation (including perception of healthy behavior benefits, negative emotions, social and family role motivation), and health promotion behavior support (including work and life pressure, family support, peer communication and mutual assistance, and medical professional support). Conclusion Patients with long COVID have a positive attitude towards health promotion behavior, but there are many influencing factors. It is necessary to improve the cognition of patients with long new crowns and their health promotion behaviors, and constantly improve the guidance of health behaviors of patients with long new crowns to promote their health. (目的 探讨新型冠状病毒感染长期症状(简称“长新冠”)患者健康促进行为及其影响因素, 为构建干预方案提供参考。方法 采用目的抽样法对15名长新冠患者进行半结构式访谈, 根据 Colaizzi七步分析法对访谈资料进行分析, 提取主题。结果 共获得3个主题: 健康行为能力(包括认知有限, 自控力低下, 身体能力, 健康素养), 健康行为动机(包括感知健康行为益处, 消极情绪, 社会和家庭角色动力), 健康促进行为支持(包括工作生活压力, 家庭支持, 同伴交流互助, 医疗专业支持)。结论 长新冠患者对健康促进行为总体持积极态度, 但影响因素较多。应提高长新冠患者对长新冠及健康促进行为的认知, 需不断完善长新冠患者健康行为的指导, 促进其健康。)